(3GdYhGed GdfMhjIs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s ((3YHOGdQMef Hf GdMGL eMeO s)
(3ChdgG (B:s
(3hHYO, aGYde Cfg dGHO dcd WGdH eYQaI GdEYQGH ef eYQaI eFI TF, SJhf efgG jSei YGedkG s
(3BNQgG (B:s
(3hEf de jXgQ hde ojbOQ aj BNQg jSei eMcjkG fMh JhcdfG Ydi ef dG jCJj GdNjQ EdG ef LgJg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B410 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B229 s
Keywords: (3GdfMhs